Inequalities and Impacts on Poverty Incidence of Tobacco, Alcohol, and Health Out-of-Pocket Expenditures in the Philippines, 2012–2018 - Haw, Nel Jason (Archīum Ateneo, 2023)
The Philippines increased taxes for tobacco and alcohol products and expanded population coverage under the national social health insurance scheme from 2012 to 2018. This paper examines inequalities in tobacco, alcohol, and health out-of-pocket (OOP) expenditures in the Philippines using the Family Income and Expenditure Survey 2012, 2015, and 2018. Fewer households reported spending on tobacco and alcohol, and the amount decreased among poor households over time, resulting in a decrease in impoverishment. Tobacco and alcohol spending was regressive, with the magnitude of regressivity decreasing between 2015 and 2018. Health OOP expenditures decreased between 2015 and 2018, with the magnitude of progressivity unchanged across time. Early evidence from this study suggests that the Philippines may have made some gains in reducing the inequitable effects of tobacco and alcohol spending on poorer households because of these policy reforms. Further analyses may be conducted to confirm whether these changes are affected by universal health coverage (UHC) policy reforms.